The Daily Mile as a public health intervention: a rapid ethnographic assessment of uptake and implementation in South London, UK - Benjamin Hanckel; Danny Ruta; Gwenda Scott; Janet L. Peacock; Judith Green (BMC, 2019)
Abstract Background Existing evidence identifies health benefits for children of additional daily physical activity (PA) on a range of cardiovascular and metabolic outcomes. The Daily Mile (TDM) is a popular scheme designed to increase children's PA within the school day. Emerging evidence indicates that participation in TDM can increase children's PA, reduce sedentarism and reduce skinfold measures. However, little is known about the potential effects of TDM as a public health intervention, and the benefits and disbenefits that might flow from wider implementation in 'real world' settings. Methods We aimed to identify how TDM is being implemented in a naturalistic setting, and what implications this has for its potential impact on population health. We undertook a rapid ethnographic assessment of uptake and implementation in Lewisham, south London. Data included interviews (n = 22) and focus groups (n = 11) with stakeholders; observations of implementation in 12 classes; and analysis of routine data sources to identify school level factors associated with uptake. Results Of the 69 primary schools in one borough, 33 (48%) had adopted TDM by September 2018. There were no significant differences between adopters and non-adopters in mean school population size (means 377 vs 397, P = 0.70), mean percentage of children eligible for free school meals (16.2 vs 14.3%, P = 0.39), or mean percentage of children from Black and Minority Ethnic populations (76.3 vs 78.2%, P = 0.41). Addressing obesity was a key incentive for adoption, although a range of health and educational benefits were also hypothesised to accrue from participation. Mapping TDM to the TIDierR-PHP checklist to describe the intervention in practice identified that considerable adaption happened at the level of borough, school, class and pupil. Population health effects are likely to be influenced by the interaction of intervention and context at each of these levels. Conclusions Examining TDM in 'real world' settings surfaces adaptions and variations in implementation. This has implications for the likely effects of TDM, and points more broadly to an urgent need for more appropriate methods for evaluating public health impact and implementation in complex contexts.